3rd European Evidence-based Consensus on the Diagnosis and Management of Crohn’s Disease 2016: Part 2: Surgical Management and Special Situations - Gionchetti, Paolo; Dignass, Axel; Danese, Silvio; Magro Dias, Fernando José; Rogler, Gerhard; Lakatos, Péter Laszlo; Adamina, Michel; Ardizzone, Sandro; Buskens, Christianne J.; Sebastian, Shaji; Laureti, Silvio; Sampietro, Gianluca M.; et al. (Journal of Crohn's and colitis, 2017)
This paper is the second in a series of two publications relating to the European Crohn’s and Colitis Organisation [ECCO] evidence-based consensus on the diagnosis and management of Crohn’s disease [CD] and concerns the surgical management of CD as well as special situations including management of perianal CD and extraintestinal manifestations. Diagnostic approaches and medical management of CD of this ECCO Consensus are covered in the first paper [Gomollon et al. JCC 2016].